PENGARUH KOMPENSASI, LINGKUNGAN KERJA, KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KEPUASAN KERJA KARYAWAN PT PG RAJAWALI 1 UNIT PG KREBET BARU MALANG - Afifah Ardiyanti Pramesti; Abdul Kodir Djaelani; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT:This study aims to determine the effect of competation, work environment, occupational safety and healt (K3) on employee satisfaction in the HR department. The research sample consisted of 61 HR employees at PT PG Rajawali 1 Unit of the New Malang Krebet using the stratified proportional random sampling method. Is a quantitative research that uses questionnaires and documentation data collection. Using multiple linier regression analisys with the help of the application SPSS 14.0 for windows. The result prove if the compensation variable, work environment, and occupational health variable do not have positive effect on job satisfaction while the safety variable had a positive effect on job satisfaction on PT PG Rajawali employees 1 Unit of the new poor Krebet Malang.Keywords: Compentation, Work Environment, Occupational Safety and Health (K3), Job Satisfaction.